Apprentissage mobile et e-santé - Abdelkader Lahmar; Nicole Poteaux (Centre National d'Enseignement à Distance, 2019)
Many mobile health application projects are focused primarily on prevention. Prevention actions in health are essentially based on education projects. However, there is little research or approach to designing digital tools that takes into account pedagogical issues. Here we focus on the potential of mobile learning in travel health counselling. In particular, we are conducting a reflection in order to give avenues to better know how to take into account educational issues during the design process of a mobile travel health consulting application. To respond, we adopted a qualitative approach by conducting focus groups with travellers and educators. The results obtained find known elements, in particular the importance of the perception of the value of the task, often weak among travellers. They also provide an innovative point of view and practical advice on how to take into account pedagogical issues, while giving a perspective of inclusion of this educational approach in the process of designing a mobile educational application.